Structural bamboo design in east Africa - Myers, Evan T. (Kansas State University, 2013)
This document addresses East Africa's need for safe, sustainable, and affordable housing and promotes use of bamboo as a structural material by providing adequate information and resources to evaluate the strength of bamboo. East African housing is a leading issue for the region because of the population growth, specifically in urban areas where housing resources and infrastructure cannot match the population growth. The solution may be bamboo housing as an alternative to urban slums. The bamboo species Oxytenanthera abyssinica is available throughout East Africa region and has been accepted and implemented in traditional housing throughout the region. This document references the resources provided by the International Code Council (ICC), International Organization for Standardizations (ISO), and International Network for Bamboo and Rattan (INBAR) for the use of bamboo as a structural material in buildings. This paper also discusses the mechanical strength of bamboo, and the structural behavior of bamboo in buildings. In addition, bamboo construction shows the tools, connections, and preservatives used in the field. The design example, using Oxytenanthera abyssinica, provides the traditional layout and materials for an Amhara house, and calculations show the practicality of bamboo in structural design. This document has led to recommendations for engineers and the bamboo industry, including the development of a codebook for bamboo design, promoting bamboo farms and plantations, creating a uniform connection, and increasing bamboo's service life. From research, bamboo is in need of further development before being considered a viable structural material to provide for commercial use but would suffice for the housing shortage in East Africa.
Keywords: Bamboo; Structural engineering; Oxytenanthera abyssinica; African Studies (0293); Architectural engineering (0462); Civil Engineering (0543)